2005
DOI: 10.1038/sj.ijo.0803108
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutathione conjugate transport: a possible compensatory protection mechanism against oxidative stress in obesity?

Abstract: Objective: To compare glutathione S-conjugate transport in obese and nonobese persons, and how glutathione S-conjugates are involved in the antioxidant status in obesity. Materials and methods: The efflux of glutathione conjugates and malondialdehyde (MDA) levels were measured in erythrocytes of obese (N ¼ 33) and nonobese (N ¼ 28) persons at every 30 min during a 120 min incubation time in vitro. 2,4-dinitrophenyl-S-glutathione (DNP-SG) represented the glutathione S-conjugate. Results: The efflux of conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Thus, tGSH levels were inversely correlated to BMI values (linear regression analysis: R 5 À0.448). This is in line with previous reports on lower erythrocyte glutathione levels in obese subjects, compared to non-obese controls [14] and with an inverse correlation between GSH levels and body weight/BMI [15].…”
Section: Introductionsupporting
confidence: 91%
“…Thus, tGSH levels were inversely correlated to BMI values (linear regression analysis: R 5 À0.448). This is in line with previous reports on lower erythrocyte glutathione levels in obese subjects, compared to non-obese controls [14] and with an inverse correlation between GSH levels and body weight/BMI [15].…”
Section: Introductionsupporting
confidence: 91%
“…The loss of antioxidant capacity is another hallmark of obesity [57]. The tripeptide thiol antioxidant glutathione has been found at reduced levels in serum and various body tissues of obese individuals [58][59][60]. Of note, low glutathione levels have also been observed in the semen of men with various infertility diagnoses [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…In the erythrocyte, major thiol GSH is the important reducing agent and antioxidant, and is involved in maintaining the cellular oxidation-reduction balance, and has been shown to protect cells from a wide variety of endogenous and exogenous insult. Ozaydin et al 22 reported that the erythrocyte GSH level was lower in obese subjects than in controls, and erythrocyte GSH-conjugate transport may increase in obesity-induced oxidative stress. Plasma metabolic parameters were also signif- icantly correlated with oxidative and antioxidant markers in this study.…”
Section: Discussionmentioning
confidence: 99%